Policy Scheme for Housing Provision in Improving Welfare: A Case Study on ASN (State Civil Apparatus) - Ika, Syahrir; Nasution, Lokot Zein (Jurnal Ekonomi Pembangunan, 2019)
Provision of decent and affordable housing in Indonesia has been faced with difficulty due to lower level of housing accessibility from the housing schemes submitted to the free market. Limited access to housing presents a significant impact on low level of community welfare. Based on these problems, this study aims to analyze the proper housing provision policy scheme in improving the welfare of the community. This study raises the case of ASN as one of the with no home ownership, especially for ASN with low rank / class. Based on the results of descriptive statistical analysis, housing provision is advised to address the preferences of beneficiaries, including priorities such as: (i) easy access to public services; (ii) proximity to work location; and (iii) adjusted to the level of position. Based on the existing regulations, there are two relevant schemes, including: FLPP and Tapera schemes. However, both have limitations, particularly those related to the limitations of Low-Income Communities (MBR). If the government prefers FLPP or Tapera scheme, thus the regulation (PP) on Tapera is advised to be altered to increase the MBR income limit. The results of this study suggest the importance of further research on alternative schemes in developing the best housing finance schemes for the future.